ChemInform Abstract: Multifunctional "Click" Prolinamides: A New Platform for Asymmetric Aldol Reactions in the Presence of Water with Catalyst Recycling. Issue 27 (13th June 2013) - Paladhi, Sushovan; Das, Joydeb; Mishra, Pratyush Kumar; Dash, Jyotirmayee
Abstract The novel prolinamide catalyst shows excellent isolated yields, enantioselectivities, and diastereoselectivities for the title reaction.